Dietary protein and energy requirements of laying quails reared under different nutrient schedule during starting and growing period - SHRIVASTAV, A K; JOHARI, T S; RAJU, M V L N (The Indian Journal of Animal Sciences, 2013)
Quail layer diets with 3 protein levels (19,22 and 25%) and 2 energy levels (2,500 and 2,750 Kcal ME/kg), were evaluated, in a factorial design, to determine the protein and energy requirement of quail layers reared on 2 different feeding schedules during starting and growing periods up to 5 weeks employing protein levels of either 27% starter and 24% grower or 24% starter and 20% grower. Per cent egg production was low with the feeding schedule consisting of low protein levels and was unaffected by protein and energy levels of layer ration. Egg weight decreased at the highest level of 25% protein, while egg mass was not affected. Feed intake decreased at higher ME level. Protein and energy intake showed direct and invert relationship, respectively, with their respective dietaty levels. Nutrient utilization decreased with increased dietary concentrations.